Genetic diversity of squash landraces (Cucurbita maxima) collected in Andean Valleys of Argentina = Diversidad genética de poblaciones de zapallo (Cucurbita maxima) colectadas en los valles andinos de la Argentina - Lorello, Ines Maria; Garcia Lampasona, Sandra Claudia; Peralta, Iris Edith (Facultad de Ciencias Agrarias, Universidad Nacional de Cuyo, 2020)
Squash landraces (Cucurbita maxima) are maintained by small farmers as a major nutritional food. Twenty seven of these landraces were collected in Argentinian Andean Valleys and morphologically characterized. Genetic diversity was evaluated with microsatellite markers designed for Cucurbita pepo and Cucumis melo and evaluated for the first time in C. maxima. Seven microsatellite primers detected 26 alleles with 3.10 average alleles per locus. The Genetic Diversity reached an average of 0.26; a Polymorphic Information Content (PIC) of 0.20 and 45.5% of polymorphic loci. Higher diversity was found at intra population level. No evidence of lineal correlation between the observed diversity and the geographical distribution of squash landraces was found. Results demonstrate a moderate genetic diversity for all populations, with a wide range of variation in different groups. A subgroup of 10 populations with the highest levels of genetic diversity was considered for maintenance within core collections in the Vegetable Crop Germplasm Bank of Agricultural Research Station (EEA) La Consulta, Mendoza, National Institute of Agricultural Technology (INTA). Anthropogenic and environmental processes, mainly abandonment of cultivated areas and frequent droughts could erode squash landraces diversity. Conservational strategies and new collecting expeditions can be decided based on the genetic diversity found.